2020
DOI: 10.1155/2020/6979105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupoints Dual‐Frequency Low‐Level Laser Therapy on Knee Osteoarthritis

Abstract: Background. Knee osteoarthritis (OA) presented with knee pain and limitation of mobility is common, and it may become a chronic problem resulting in major loss of function, with related impaired activity of daily living. Current traditional therapy for knee OA includes pharmacological treatment and physiotherapy, but the efficacies are limited. An alternative noninvasive treatment low-level laser therapy (LLLT) applied to acupoints is still contradictory and the efficacy needs to be assessed. Methods and Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Clinical research has demonstrated that low-level laser therapy (LLLT) has an effect within the fields of dermatology, orthopedics, and neurology [7][8][9][10][11]. In ophthalmology, LLLT was also effective in amblyopia in the early stage [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research has demonstrated that low-level laser therapy (LLLT) has an effect within the fields of dermatology, orthopedics, and neurology [7][8][9][10][11]. In ophthalmology, LLLT was also effective in amblyopia in the early stage [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies by Fernanda R. et al [ 18 ], Leyla K. et al [ 19 ], Mariana M. et al [ 20 ], De Souza R. et al [ 21 ], Shaiane S. et al [ 22 ], Taradaj J. et al [ 24 ], and Fang-Y L. et al [ 25 ] PBMT was applied to patients with chronic pain4…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies, by Fernanda R, et al [ 18 ] and Fang-Y L. et al [ 25 ], deal with female patients, over the age of 60, with knee osteoarthritis. Both studies revealed significant improvements in the patients, with p -values less than 0.05 in all the studied variables related to chronic pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for KOA include patient education, exercise, lifestyle modifications such as weight control, orthoses, physical therapy applications, pharmacotherapy, intra-articular methods, and surgery 4 . Available traditional treatments with limited efficacy are pharmacotherapy and physiotherapy 5 .…”
Section: Introductionmentioning
confidence: 99%